Connecting Protein Conformational Dynamics with Catalytic Function as Illustrated in Dihydrofolate Reductase - Fan, Yao (2013)
Combined QM/MM molecular dynamics simulations reveal that the M20 loop conformational dynamics of dihydrofolate reductase (DHFR) is severely restricted at the transition state of the hydride transfer as a result of the M42W/G121V double mutation. Consequently, the double mutant enzyme has a reduced entropy of activation, i.e., increased entropic barrier, and altered temperature dependence of kinetic isotope effects in comparison with wild-type DHFR. Interestingly, both in the wild-type DHFR and the double mutant, the average donor-acceptor distances are essentially the same in the Michaelis complex state (about 3.5 Å) and the transition state (2.7 Å). It was found that an additional hydrogen bond is formed to stabilize the M20 loop in the closed conformation in the M42W/G121V double mutant. The computational results reflect a similar aim designed to knock out precisely the dynamic flexibility of the M20 loop in a different double mutant, N23PP/S148A.